Evaluasi Komprehensif terhadap Pengaruh Pra-perlakuan Alkali Berbantuan Gelombang Mikro Menggunakan Amonia pada Limbah Bonggol Nanas - Ningtyas, Vita Putri; Agisriani, Agferofita; Saima Perdani, Meka; Normayulisa Putri, Dwini (INDONESIAN JOURNAL OF CHEMICAL RESEARCH, 2026)
This study aims to comprehensively investigate the effect of microwave-assisted alkali pretreatment on delignification and changes in composition, functional groups, morphology, and crystallinity structure of pineapple core waste biomass. Pretreatment was carried out using 0.03 M ammonia solution through microwave heating at 600 W power for 5 minutes. Delignification and composition were determined using biomass compositional analysis method from the National Renewable Energy Laboratory (NREL), functional groups were characterized by Fourier Transform Infrared Spectroscopy (FTIR), surface morphology was characterized using a Scanning Electron Microscope (SEM), and crystallinity was characterized by the X-Ray Diffraction (XRD) method. The results showed that the alkali pretreatment with microwaves was able to reduce the lignin content from 23.443% to 19.71%, increase the hemicellulose content from 39.903% to 45.967%, and maintain the cellulose content at 34.317% from 36.653%. FTIR analysis showed a weakening of the lignin aromatic band and changes in the hydroxyl group. SEM analysis showed visible morphological changes in the biomass structure which was initially dense and regular to become rougher, cracked, and containing cavities. XRD analysis showed a decrease in the crystallinity index which indicates the occurrence of partial disruption of the cellulose crystal structure. Based on overall results, microwaves-assisted alkali pretreatment using ammonia showed effectiveness in influencing the characteristics of pineapple core biomass, especially in the delignification process and changes in biomass structure. Keywords: pineapple core waste, lignocellulose, alkali pretreatment, microwave-assisted, characterization